Multi-sensory approaches to (audio) describing the visual arts - Neves, Josélia (MonTi Monografías de Traducción e Interpretación, 2014)
Making art accessible to blind patrons requires the ability to convey explicit and implicit visual messages through non-visual forms. Audio description is often seen as the best way to offer visual texts to blind people; however, one may query whether words alone are sufficient to convey the subtleties of art and to transport the emotional charge such works offer. It is a fact that the dialogue between words and touch may allow these particular “readers” to “see” art in its tangible forms, but perhaps more is needed if one is to give them the opportunity to live the art experience to the full. This article discusses different multi-sensory approaches to making art available to visually impaired people and proposes soundpainting as a form of artistic transcreation.